Constructing the Image of Teachers as Educators in the Digital Era Through TikTok - Wibowo, Tangguh; Syafuddin, Khairul (Jurnal Komunikasi Pendidikan, 2025)
Social media undeniably contributes to changing how a teacher figure is portrayed and how communication patterns with students occur. Social media users, particularly TikTok, can upload audiovisual content of teachers and students joyfully dancing together. This research aims to present a depiction of teachers in the current digital era. It is a multidisciplinary study that examines educational and social contexts. The research method employed is semiotics by Roland Barthes. The researchers analyze the myths conveyed in the audiovisual content to unveil the image of teachers in the digital era. The results reveal the current depiction of teacher-student relationships in the context of dancing on social media, which has significant implications. It emphasizes the importance of teachers' role in assisting students in managing social media usage wisely and serving as positive role models. Through dancing content on social media, teachers can strengthen social connections with students outside the school, creating an informal space for closeness and better understanding of students as individuals.